Avaliação clínica da saúde bucal de crianças com neoplasias malignas atendidas no Hospital Infantil Varela Santiago em Natal-RN - Gordón Núñez, Manuel Antonio (2001)
The childhood cancer is characterized by a predominance of hematogenic and lymphatic system neoplasm, although a fTequency of the central nervous system tumors and sarcomas are widely common. Particularities of many childhood cancers and the adverses effect of the antineoplastic agents can change radically the oral environrnent and predisposes to the risk of oral complications. This study assessment clinically the oral health of 40 children on treatment for different types of malignant neoplasm with age range of O to 1S years old (Group I) and compared to 38 nonnal children in the same age range (Group lI). The results shown that nonnal patients had a gingival bleeding index (GBI) and caries experience minar than patients of Group lI, the visivel plaque index (VPI) was lightly higher in patients of Group 1. There was not difference statistically significant in the variables. Sixteen patients of Group I developed together 61 oral complications with predominance of mucositis, followed by spontaneous oral bleeding, candidiasis and xerostomy, that complication were most commons in patients with systemic neoplasm. Its was concluded that patients submitted to antineoplastic therapy with poor oral health had a higher risk to develop oral complications